INFORMATIVE DESCRIPTORS FOR STATISTICAL RECOGNITION OF CRYPTOGRAPHIC GENERATORS - Yu. S. Kharin; V. Yu. Palukha (Informatika)
An approach to developing informative descriptors for solving the problem of statistical recognition of cryptographic generators is proposed. The descriptors developed by this approach are given. Theoretical results are illustrated by the computer experiments.